PERSEPSI KADER POSYANDU TENTANG POSYANDU DAN SISTEM INFORMASI POSYANDU DI DESA SUKOHARJO; STUDI KUALITATIF - Tyas Ning Yuni Astuti Anggraini; Ekawati; Kharisma; Dian Puspitasari (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: In the 2020 RPJMN, main focus the government is promotive and preventive. Promotive and preventive efforts can be built from the Posyandu level. The Posyandu monitors the health conditions of mothers and children on a monthly basis. Monitoring is carried out by health cadres.Objective: To find out the perception of health cadres related to Posyandu and Posyandu information systems in Sukoharjo Village.Methods: The type of research that will be used in this research is qualitative research. The research subject is the selection of some of the Posyandu cadres in Sukoharjo Village as respondents to evaluate the quality of information between before and after system development. Sampling was done by purposive sampling. Content analysis is used to analyze qualitative data derived from the results of in-depth interviews and observations related to the development of information systems.Results: Shows that most of them are in the young category (31-47 years) by 8 people (62%), the majority of education is high school education/equivalent as many as 8 people (62%), and with work most of them are housewives as many as 9 people (69%) . Perception consists of 5 dimensions, 4 dimensions related to Posyandu as a whole, namely related to the duties of Health cadres, Posyandu implementation techniques, barriers to Posyandu implementation, and coordination of Health workers with cadres. Meanwhile, in another dimension related to the posyandu information system, the focus is on the views of cadres related to the expected posyandu information system.Conclusion: In the perception of cadres related to posyandu and posyandu information systems, there are 5 main dimensions.